UPAYA MENINGKATKAN MOTIVASI BELAJAR DAN KETERAMPILAN MENULIS TEKS ANEKDOT MENGGUNAKAN TEKNIK PEER REVIEW KELAS X MIPA 1 SMAN 2 MAGELANG - Sartono Sartono (TRANSFORMATIKA, 2015)
The purpose of this study was to determine the effectiveness of peer review technique in increasing studentsâ€™ writing motivation and to determine the effectiveness of using peer review technique to improve studentsâ€™ writing skills of anecdote text class X MIPA 1. The study is done in SMAN 2 Magelang from March â€“ April 2014. The subjects are 31 students of X MIPA 1 class, with quantitative data, the result of anecdote writing activity and qualitative data in the form of quesionare, observation result, as well as teaching document.The quantitative data collection is in the form of test and qualitative data collection is in the form of non-test. The writer uses two techniques: quantitative data with descriptive analysis; qualitative data with triangulation method. The are two cycles in this study, with four actions (planning, actuating, observing, and reflecting) in each. The study shows that: (1) Peer review technique can increase studentsâ€™ motivation from â€œfairâ€ level (2.23) to â€œgoodâ€ level (2.97); (2) Peer review technique can increase the students ability in writing anecdote text from â€œpoorâ€ level (56.77) to â€œgoodâ€ level (84.84). It is clear that by applying peer review technique, the studentsâ€™ motivation and writing skill is increased. It is invited for language teachers to use varied teaching techniques, besides that, teachers should keep trying to eliminate peer review technique weakness for the sake of effective, efficient, and enjoyable teaching learning process.Â Keyword: peer review, writing anecdote text, writing motivation.